2015
DOI: 10.1007/s40262-015-0267-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Polymorphisms of ABCB1 (MDR1, P-Glycoprotein) on Drug Disposition and Potential Clinical Implications: Update of the Literature

Abstract: ATP-binding cassette transporter B1 (ABCB1; P-glycoprotein; multidrug resistance protein 1) is an adenosine triphosphate (ATP)-dependent efflux transporter located in the plasma membrane of many different cell types. Numerous structurally unrelated compounds, including drugs and environmental toxins, have been identified as substrates. ABCB1 limits the absorption of xenobiotics from the gut lumen, protects sensitive tissues (e.g. the brain, fetus and testes) from xenobiotics and is involved in biliary and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(190 citation statements)
references
References 300 publications
(226 reference statements)
6
160
1
6
Order By: Relevance
“…ABCB1 (also known as multidrug resistance protein 1 (MDR1), P-glycoprotein 1, abbreviated as P-gp), a member of ABC transporters family, is expressed at major physiological barriers, such as intestinal epithelium, the canalicular membrane of liver cells, kidney proximal tubule epithelial cells, blood-brain barrier and blood-testis barrier, 42,43 where it exhibits protective and excretory functions. 44 Mutations in ABCB1 have been associated with changes in drug disposition, sensitivity and toxicity. 44 In our previous study, ABCB1 polymorphism was found to be correlated with Gefitinib skin toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABCB1 (also known as multidrug resistance protein 1 (MDR1), P-glycoprotein 1, abbreviated as P-gp), a member of ABC transporters family, is expressed at major physiological barriers, such as intestinal epithelium, the canalicular membrane of liver cells, kidney proximal tubule epithelial cells, blood-brain barrier and blood-testis barrier, 42,43 where it exhibits protective and excretory functions. 44 Mutations in ABCB1 have been associated with changes in drug disposition, sensitivity and toxicity. 44 In our previous study, ABCB1 polymorphism was found to be correlated with Gefitinib skin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…44 Mutations in ABCB1 have been associated with changes in drug disposition, sensitivity and toxicity. 44 In our previous study, ABCB1 polymorphism was found to be correlated with Gefitinib skin toxicity. 45 We, for the first time, examined the association of ABCB1 rs2235040 CT genotype with periorbital oedema in GIST patients treated with Imatinib, finding it a valuable protective factor in predicting this toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Since many of these transcription factors are altered by stress signals, ABCB1 is highly susceptible to upregulation during a stress response. ABCB1 expression can also be modified by single nucleotide polymorphisms (SNPs) [91, 92], which play a very important role in the context of cancer therapy, as well as by gene rearrangements [93], mutations [82, 94], epigenetic regulation [95, 96] and post-translational mechanisms [97]. …”
Section: Multidrug Resistancementioning
confidence: 99%
“…Respective warnings are included in labels of several drugs, which are ABCB1 substrates. To what extent genetic variants in the ABCB1 gene affect clinical drug response is still inconclusive because study results are in part controversial and/or do not provide sufficient evidence to affect treatment decisions [3]. Therefore, further large-scale studies are warranted to determine the relevance of ABCB1 genetics to precision medicine.…”
Section: Clinical Consequences Of Interindividual Variability Of Tranmentioning
confidence: 99%
“…The SLC superfamily comprises uptake as well as efflux transporters [2]. In contrast, members of the ABC transporter family are predominantly efflux transporters [3]. Interindividual variability of SLC and ABC transporter expression and function thus contributes to differences in treatment efficacy or the occurrence of adverse drug reactions (ADRs).…”
Section: Introductionmentioning
confidence: 99%